Hierarchical micro/nanoporous ion-exchangeable sponge. Issue 3 (12th December 2019) - Choi, Jihye; Lee, Hyomin; Kim, Sung Jae
Abstract : The hierarchical micro/nanoporous sponge can desalt and neutralize a water source by squeezing the sponge in a single hand grip. Abstract : Inspired by the versatile properties of a sponge, we propose an ion-exchangeable sponge composed of hierarchical micropores and nanopores for water treatment. Sodium ions in brackish water (10–300 mM) absorbed in the sponge were exchanged for hydrogen ions in a short incubation time and the desalted water was released by squeezing the sponge with a single hand grip. This simple desalination process was attributed to the multi-scale porous structures in the sponge. A number of nanoporous thin films were formed like bubbles surrounded by the closed backbone of the microporous sponge. The hierarchical micro/nanopores maximized the contact area of the ion-exchanging surface with the saline solution so that scaled-up desalination was achieved. Furthermore, the growth of wheat shoots in the desalted water was demonstrated in vivo after using this micro/nanofluidic based water-treatment with the sponges. Wheat shoots grown in NaHCO3 /Na2 CO3 solutions treated by the sponges were 110 to 226.45% longer than those grown in the original salty water. This implies that the ion-exchangeable sponge could serve as an appropriate technology for the treatment of ground water affected by acid rain and weathered alkaline rocks.